2019
DOI: 10.1103/physrevlett.122.048102
|View full text |Cite
|
Sign up to set email alerts
|

DNA Crookedness Regulates DNA Mechanical Properties at Short Length Scales

Abstract: Sequence-dependent DNA conformation and flexibility play a fundamental role in the specificity of DNA-protein interactions. Here we quantify the DNA crookedness: a sequence-dependent deformation of DNA that consists of periodic bends of the base pair centers chain. Using extensive 100 μs-long, all-atom molecular dynamics simulations, we found that DNA crookedness and its associated flexibility are bijective, which unveils a one-to-one relation between DNA structure and dynamics. This allowed us to build a pred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(111 citation statements)
references
References 62 publications
7
104
0
Order By: Relevance
“…Our data suggests that for creating a regular pattern characteristic of the curved fragment, a frequency with an exact number of cycles per DNA-turn at the single bp-step level is needed (3 cycles per DNA-turn for the 52mer in front of 3.5 for the 62mer, see Figure 6), so local bends can couple for building up a significant curvature. Our results are in the same line of others that highlighted the importance of periodicity 36 for understanding the special mechanical properties of A-tracts 24 or nucleosome-positioning sequences. 65,66 Figure 6: Top: length-evolution of bending angle profiles along the sequence for the most (left) and less (right) curved oligomers (52mer and 62mer, respectively).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our data suggests that for creating a regular pattern characteristic of the curved fragment, a frequency with an exact number of cycles per DNA-turn at the single bp-step level is needed (3 cycles per DNA-turn for the 52mer in front of 3.5 for the 62mer, see Figure 6), so local bends can couple for building up a significant curvature. Our results are in the same line of others that highlighted the importance of periodicity 36 for understanding the special mechanical properties of A-tracts 24 or nucleosome-positioning sequences. 65,66 Figure 6: Top: length-evolution of bending angle profiles along the sequence for the most (left) and less (right) curved oligomers (52mer and 62mer, respectively).…”
Section: Resultssupporting
confidence: 92%
“…And finally for the persistence length, we found that tangent-tangent correlation presented periodic behavior reflecting the static curvature of DNA helix in agreement with others. 31,[33][34][35][36] Without considering these modulations, the decay was close to the consensus value of 50 nm. [6][7][8][9][10] Here we present SerraNA, which is an open-source, versatile and integrated implementation of the LDEM, that calculates the overall elastic constants of helical nucleic acids (NA) and the elastic/ structure profiles for every possible sub-length (serra from Latin means "mountain range").…”
supporting
confidence: 55%
See 1 more Smart Citation
“…6), so local bends can couple for building up a significant curvature. Our results are in the same line of others that highlighted the importance of periodicity 32,72,73 for understanding the special mechanical properties of A-tracts 19 or nucleosome-positioning sequences. [74][75][76] Protein-DNA and sequence mismatch SerraNA has the capacity to deal with perturbed DNA molecules caused by a series of factors like sequence mismatch or protein binding.…”
Section: Stretch Modulussupporting
confidence: 92%
“…11,12,27,29 Highly soft stretch modulus measured by SAXS experiments on short oligomers 31 was observed to be caused mainly by end effects. 27 For the persistence length, we found that the periodic tangent-tangent correlation reflected the ''crookedness'' 32 of the static curvature of the DNA helix 26,27,29,30,[32][33][34][35] and, without considering these modulations, the decay was close to the consensus value of 50 nm. [6][7][8][9][10] Thus, the LDEM is suitable for describing the average mechanical properties of DNA and, from this perspective, it was applied to test the DNA force-field for atomic simulations, Parmbsc1.…”
Section: Introductionmentioning
confidence: 75%